2004
DOI: 10.1111/j.1752-7325.2004.tb02723.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Tooth Loss in Two US Adult Populations

Abstract: Over a 10-year period, the incidence of tooth loss, the rates of tooth loss, and the predictors of tooth loss were found to vary by population and by sex. These results illustrate the limits of generalizing tooth loss findings across different study cohorts and indicate that there may exist important differences in risk factors for tooth loss among US adult populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
81
2
7

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(102 citation statements)
references
References 20 publications
12
81
2
7
Order By: Relevance
“…The data are consistent with previous reports [4][5][6][7][8]. Education and paternal social class are likely to be indices of childhood socio-economic resources [11], potentially confounding each other, and support the need for a lifecourse approach to health status in old age.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The data are consistent with previous reports [4][5][6][7][8]. Education and paternal social class are likely to be indices of childhood socio-economic resources [11], potentially confounding each other, and support the need for a lifecourse approach to health status in old age.…”
Section: Discussionsupporting
confidence: 81%
“…A number of risk factors for tooth loss have been identified. These include both sexes (both male [4] and female [5] have been reported as having an increasing risk), education [6,7], social class [5,8], alcohol consumption [4,6] and cigarette smoking [5,6]. Some of these risk factors-social class, alcohol consumption and smoking-occur mainly in adulthood.…”
Section: Sir-mentioning
confidence: 99%
“…9 In the United States, an association between smoking and tooth loss has been identified. 6,[10][11][12][13][14][15][16] Such an association was also found in subjects residing in Sweden, [17][18][19] Australia, 20 Iceland, 21 Jordan, 22 Brazil, 23 and Kuwait. 24 In South-East Asian countries, only a few studies have reported on the association between smoking and tooth loss.…”
Section: Methodsmentioning
confidence: 94%
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] Data indicated that the prevalence rate of PDD, worldwide, varied from 37% to 77%, depending on age of onset, oral hygiene, and other risk factors, underlying dental problems, smoking and diabetes. [21][22] …”
Section: Discussionmentioning
confidence: 99%
“…Bad habit like mouth breathing 8.0%,tongue thrusting 1.0%, lip biting 3.0%, pencil biting 12.0% and Brushing 13.0% observed among the respondents. Some study revealed that Dental and oral health are affected by diet and certain aspects of lifestyle [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] .…”
Section: Discussionmentioning
confidence: 99%